2014
DOI: 10.1097/cji.0000000000000015
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Erlotinib Plus Dendritic Cells and Cytokine-induced Killer Cells in Maintenance Therapy of Advanced Non–Small Cell Lung Cancer

Abstract: The aim of this study was to evaluate the safety and effectiveness of erlotinib plus DC/CIK in maintenance therapy of advanced non-small cell lung cancer. After 4 cycles of the 2-drug regimen treatment with platinum, the 54 patients with non-small cell lung cancer in phase IIIb or IV reached stable or beyond stable stages. The patients were then randomly divided into 2 groups. One group was treated with erlotinib therapy (erlotinib group), and the other was treated with DC/CIK plus erlotinib (DC/CIK plus erlot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…However, it is unclear whether treatment-related pyrexia might exploited as a indicator for identification of cancer patients who would benefit from DC-CIK immunotherapy. Currently, a large body of clinical trials suggested that there was neither serious AEs nor death caused by DC-CIK immunotherapy [26][27][28][29][30][31]. Although we did not find serious AEs in this meta-analysis, the eligible articles were all from Asia and lack multinational clinic trials.…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…However, it is unclear whether treatment-related pyrexia might exploited as a indicator for identification of cancer patients who would benefit from DC-CIK immunotherapy. Currently, a large body of clinical trials suggested that there was neither serious AEs nor death caused by DC-CIK immunotherapy [26][27][28][29][30][31]. Although we did not find serious AEs in this meta-analysis, the eligible articles were all from Asia and lack multinational clinic trials.…”
Section: Discussionmentioning
confidence: 59%
“…The use of DC-CIK immunotherapy with or without chemotherapy in NSCLC has been evaluated by previous clinical trials, but the clinical outcomes differ significantly [26][27][28][29][30][31]. Thus, it is unknown if DC-CIK immunotherapy is effective or safe for patients with NSCLC.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations